Performance appraisal: the development of a multi-criteria management tool based on Erdogan's model. (23rd December 2014) - De Felice, Fabio; Petrillo, Antonella; Tricarico, Michele
An organisation's performance depended on its people and their competencies. Performance appraisal represents the most important factor in human resource management, as well as in the strategic management. This article proposes a reference model to assess performance of human resource for the supervision and management of horse racing in the appraisal context. The present paper uses Erdogan's model and analytic hierarchy process (AHP), a research method to support rational decision-making on several qualitative factors, to evaluate human performances and provides a way to rank the alternatives of the problem by deriving priorities. The proposed model can be used for all of the assessment processes while the decision of the criteria and sub criteria can be changed in accordance to the management agreement.